Pré-Habilitação em Doentes Oncológicos: Relatório de Estágio - Bruno Faria Aguiar (2024)
Introduction: Prehabilitation in the oncological context, particularly in patients with locally advanced gastric adenocarcinoma, aims to optimize functional capacity, nutritional status, and psychological health before surgical interventions. This report describes the implementation of the FORTALECER EM CASA/PROTECT clinical trial, developed at the Portuguese Oncology Institute of Porto (IPO-Porto), which compared the effectiveness of two physical exercise protocols (structured versus non-structured), performed at home, with the goal of improving postoperative recovery and reducing complications associated with surgery and chemotherapy. Objectives: The main objective of this study was to evaluate the impact of a structured home-based physical exercise program compared to a non-structured program on functional recovery and the reduction of postoperative complications in patients with gastric adenocarcinoma undergoing neoadjuvant chemotherapy and surgery. Methodology: This randomized clinical trial included 179 patients, of which 99 completed all phases of the study. Participants were randomly divided into two groups: one group followed a structured physical exercise program, while the other followed a nonstructured program. Monitoring included regular assessments of functional capacity, frailty levels, quality of life, and postoperative complications. Data were collected through physical activity monitoring devices (smartbands), questionnaires on mental and physical health status, and functional tests. Results: The results clearly showed that patients who adhered to the structured program had a significant improvement, not only in functional capacity but also in reduced hospital stay and need for intensive care. Furthermore, postoperative recovery was faster, and fewer postoperative complications were observed compared to the group that followed the non-structured program. Adherence to the program varied according to age and initial frailty status. Conclusion: This study reveals that prehabilitation, through an organized physical exercise program, is an effective intervention in preparing for surgery in cancer patients, contributing to a reduction in postoperative complications and ensuring faster recovery. This analysis highlights the importance of integrating prehabilitation programs into the treatment of patients diagnosed with gastric adenocarcinoma.